DEVELOPING AND VALIDATING A MODEL MEDIATING THE IMPACT OF THE ABROAD TRAINING AND THE SAUDI PUBLIC EMPLOYEES CREATIVITY - Mohamad Kenan Assi; Valliappan Raju (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research adopts a scientific approach to determine the impact of involving abroad training quality as a mediator between the constructs of the abroad trainee factors and abroad training factors and the creativity of Saudi public employees who attend at least one training session. The training was held in Istanbul, Dubai, and Kuala Lumpur in 2018, and an equal probability random sampling technique was adopted by involving all recipients of the training sessions whose net number was 385 respondents. Data collection was performed by either direct collection or an online survey. A questionnaire was based on previous studies and tested for validity and reliability by using content validity, face validity, and pilot study. Data obtained from the survey was analyzed by utilizing the software Statistical Package for the Social Sciences (SPSS 22) and SmartPLS 3.0. The results have shown that half of the six subhypotheses was supported when training did not consider AT. However, when AT was involved, only one sub-hypothesis was rejected, and the other five sub-hypotheses were supported. Moreover, when the impact of AT on EC was directly tested, it was found supported; however, with a weak association (0.330) compared with the corresponding association under AT involvement (0.803). The result could play an important role in setting future abroad training sessions as the involvement of a mediator makes a big difference in the achievement of the employees that would benefit the organizations where employees were coming from.